Poultry sellers’ perception and their effort for prevention strategy on avian influenza in Banda Aceh, Indonesia - . Darmawi; Teuku R. Ferasyi; . Muthmainnah; Ummu Balqis; . Fakhrurrazi; . Darniati; Muhammad Hambal (Syiah Kuala University, 2012)
A study was conducted to examine some poultry sellers’ perception of the Avian influenza (birdflu) in nine locations (Ulee Kareng, Batoh, Lamnyong, Kampong Baru, Peunayong, Setui, Kampong Ateuk, and Neusu) in Banda Aceh Municipality, Indonesia. Primary data were obtained with the use of a structured questionnaire administared to ninety nine (99) respondents selected using proportional stratified random sampling, between November to December 2011. Information was obtained using the questionnaire sheets contain questions: knowladge, attitude, availability of facilities, and the effort of Avian influenza prevention strategy. Data obtained were analyzed by descriptive statistics. The result showed that only 52% of the poultry sellers’ had good knowledge of early symptomps of Avian influenza. Amount 59% of the poultry sellers’ had good attitudes. Result also showed that 73% of respondents had good facilities that was available in live poultry market area, but only 70% of respondents were good awareness about the effort of Avian influenza prevention strategy. In addition, the respondents who had more knowledge, good attitudes, and/or good facilities were also those who actually acted more preventively. Based on the result we concluded that the poultry sellers’ perception on prevention strategy for infection of birdflu in Banda Aceh categorized as poor. It is suggested that compliance with preventive measures may be enhanced through behavioural modification and building awareness through communication, training, workshop programs to the live poultry market sellers’ in Banda Aceh